Elevated Cerebral Blood Flow and Volume in Systemic Lupus Measured by Dynamic Susceptibility Contrast Magnetic Resonance Imaging - Gasparovic, Charles M. (2010)
OBJECTIVE: Several studies have examined abnormalities in cerebral blood flow (CBF) in patients with systemic lupus erythematosus (SLE). However, the majority of these studies have reported CBF relative to a region assumed to be normal in the brain. The purpose of the present study was to examine absolute differences in both regional CBF and cerebral blood volume (CBV) between SLE patients and healthy control subjects. METHODS: CBF and CBV were measured with dynamic susceptibility contrast (DSC) magnetic resonance imaging (MRI), a technique that provides an alternative to radionuclide perfusion studies and permits quantitative anatomic, CBF, and CBV imaging in a single scanning session. CBF and CBV were measured in both lesions and normal appearing tissue in the major cerebral and subcortical brain regions. Unlike most past perfusion studies on SLE, CBF and CBV values were not normalized to a region of brain assumed to be healthy. RESULTS: As expected, CBF and CBV within MRI-visible lesions were markedly reduced relative to surrounding normal appearing white matter. However, both CBF and CBV in normal appearing tissue were higher in SLE patient groups, with or without lesions, relative to the control group. CONCLUSION: DSC MRI, without normalization to a region presumed to be healthy, revealed that CBF and CBV in normal appearing tissue in SLE patients is higher than CBF and CBV in control subjects. Since this finding was made in subgroups of patients with and with out lesions, the higher CBF and CBV appears to precede lesion pathology.